文本研究的證明方法反省——以成文法及普通法法統對《大清商律》 法律思想的影響爲例: A review on the methods of interpretations, the case of the legislative effects of statute and common law systems on the theories of Daqingshanglu
<span data-sheets-value=""1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English."" data-sheets-userformat=""2":705,"3":"1":0,"9":0,"10":1,"12":0" data-sheets-validation-definition=""1":"1":"1":24,"2":["1":0,"5":"1":"1":0,"2":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English." ,"1":0,"5":"1":"1":0,"2":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only." ],"2":"1":"1":["1":4,"6":0,"1":2,"3":"TRIM","4":1,"1":3,"5":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English." ,"1":3,"5":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only." ,"1":2,"3":"ARRAY_ROW","4":2,"1":2,"3":"ARRAY_LITERAL","4":1,"1":2,"3":"TRIM","4":1,"1":2,"3":"EXACT","4":2,"1":2,"3":"OR","4":1,"1":2,"3":"ARRAYFORMULA","4":1,"1":1,"2":"="],"3":"R0]FTRIM:1]LSLANGUAGE NOTE | Document text in Chinese; abstract also in English.]]LSLANGUAGE NOTE | Document text in Chinese only.]]FARRAY_ROW:2]FARRAY_LITERAL:1]FTRIM:1]FEXACT:2]FOR:1]FARRAYFORMULA:1]S","3":["1":"1":0,"2":1,"3":0,"4":1,"5":1118464,"2":0],"2":"","3":0,"4":1" data-sheets-validation-id="0">LANGUAGE NOTE | Document text in Chinese; abstract also in English. 任何文本思想的闡發，都離不開詮釋的過程。本文藉著探討清末頒行通用的《大清商律》法律思想的繼受問題，檢示在人文研究中，一些用來詮釋及證明思想間承傳關係的方法，其效果若何。 《大清商律》的法律思想並非源自傳統中國律令，而是繼受自當時中國以外的成文法和普通法統。學界或點算當中歸屬不同思想的條例的數量；或透過分析條例中屬於成文法統的特徵，而多認爲此法乃以成文法爲主導思想。 本文透過重新檢示這兩種辨别法律思想的方法，認爲看似最爲直接的點算方式，會因概念内涵不能明確區分，而根本不能點算内容所屬。至於特徵性證明固然是一項重要工具，但本文發現當中屬成文法的特徵，並不基於爲倣效該法所致，而反與當時清政府希望法制獨立的意願有關。因此這兩種方法，似乎均有其弊處。本文進一步透過分析《大清商律》的制訂背景，提出以普通法爲主導思想的説法，並反省文本出現之背景，於詮釋文本是結合證成之作用。 Daqingshanglu published in 1904, is considered as the first implemented business law in China. It is believed that its legislative thoughts inherited those from both statute and common law systems outside the country while it is significantly influenced by statute law systems. Fellow researchers make such conclusion by simply labelling the statute law-charactised articles and showing the features of such law which belongs to statute law system. This paper, however, reviews the above methods and argues the indifference of both law systems makes labelling the characterized articles is nearly impossible. Meanwhile, the features which belong to statute law system of Daqingshanglu should also be regarded as a diplomatic decision to please the countries under the statute law system by the Qing government, instead of a result of pure legislative actions. This paper further discusses Daqingshanglu is more possibly inherited legal theories from common law system by reviewing the legislation background of it. This reminds fellow researchers for the limitations of the above common interpreting methods and the importance of reviewing the background of a text whilst conducting humanities researches. , journal=人文中國學報, author=馮樹勳, year=2011, month=Sep., pages=577–624